QUALITY MANAGEMENT FOR ZERO DEFECT IN SCHOOL BASED PESANTREN - Tohet, Moch.; Ma'unah, Zahrotul (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The problem faced by Indonesia today is the low quality of education. Quality education is the hope and demand for all stakeholders. Therefore, Nurul Jadid High School seeks to apply the right strategy to improve quality to produce superior graduates in formality, religion and morals. Nurul Jadid High School implements a quality management strategy for zero defects to achieve this goal. The strategy emphasizes doing everything right from the program's start, which aims to reduce the possible minor mistakes in building quality education. This study aims to determine how important the quality of education has been implemented in institutions under the auspices of the Nurul Jadid Islamic boarding school. The research was conducted using a qualitative approach through case study research. The data were obtained from the observation process, interviews with the principal of SMA Nurul Jadid, and interviews with several staff in each institution. The data that has been collected is analyzed using the Miles and Huberman data analysis technique, which consists of data reduction, data display, and verification. The results of this study indicate that the quality management process for zero defects based on Islamic boarding schools to improve the quality of education is carried out through; quality management planning for zero defects, quality management assurance for zero defects, and quality management control for zero defects. Keywords: Educational Institutions, Islamic Boarding Schools, Quality, Zero Defect